Encapsulation of Docosahexaenoic Acid Oil Substantially Improves the Oxylipin Profile of Rat Tissues - Wang, Jun; Ossemond, Jordane; Le Gouar, Yann; Boissel, Françoise; Dupont, Didier; Pédrono, Frédérique (Frontiers in Nutrition, 2022)
Docosahexaenoic acid (DHA) is a major n-3 polyunsaturated fatty acid particularly involved in cognitive and cardiovascular functions. Due to the high unsaturation index, its dietary intake form has been considered to improve oxidation status and to favor as well bioaccessibility and bioavailability. This study aimed at investigating the effect of DHA encapsulated with natural whey protein. DHA was dietary provided as triacylglycerols to achieve 2.3% over total fatty acids. It was daily supplied to weanling rats for four weeks in omelet as food matrix, consecutively to a 6-hour fasting. Firstly, when DHA oil was encapsulated, consumption of chow diet was enhanced leading to promote animal growth. Secondly, brain exhibited a high accretion of 22.8% DHA, which was not improved by dietary supplementation of DHA. Encapsulation of DHA oil did not greatly affect the fatty acid proportions in tissues, but remarkably modified the profile of oxidized metabolites of fatty acids in plasma, heart and even brain. Specific oxylipins derived from DHA were upgraded, such as Protectin Dx in heart and 14-HDoHE in brain, whereas those generated from n-6 polyunsaturated fatty acids were mainly mitigated. This effect was independent of oxylipins present in DHA oil since absent after food processing. Collectively, these data suggested that dietary encapsulation of DHA oil triggered a more efficient absorption of DHA, the metabolism of which was enhanced more than its own accretion in our experimental conditions. Incorporating DHA oil in functional food may finally improve the global health status by generating precursors of protectins and maresins.